Disentangling the intricate atomic short-range order and electronic properties in amorphous transition metal oxides - C. A. Triana (Nature Portfolio, 2017)
Abstract Solid state materials with crystalline order have been well-known and characterized for almost a century while the description of disordered materials still bears significant challenges. Among these are the atomic short-range order and electronic properties of amorphous transition metal oxides [aTMOs], that have emerged as novel multifunctional materials due to their optical switching properties and high-capacity to intercalate alkali metal ions at low voltages. For decades, research on aTMOs has dealt with technological optimization. However, it remains challenging to unveil their intricate atomic short-range order. Currently, no systematic and broadly applicable methods exist to assess atomic-size structure, and since electronic localization is structure-dependent, still there are not well-established optical and electronic mechanisms for modelling the properties of aTMOs. We present state-of-the-art systematic procedures involving theory and experiment in a self-consistent computational framework to unveil the atomic short-range order and its role for the electronic properties. The scheme is applied to amorphous tungsten trioxide aWO3, which is the most studied electrochromic aTMO in spite of its unidentified atomic-size structure. Our approach provides a one-to-one matching of experimental data and corresponding model structure from which electronic properties can be directly calculated in agreement with the electronic transitions observed in the XANES spectra.